Penyajian Pendapatan Komprehensif Lain Dan Komponennya Pada Industri Keuangan - Yudy Dwi Santoso; Nurmala Ahmar; JMV Mulyadi (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2017)
This research was conducted with the aim to analyze the presentation of the components of other comprehensive income / other comprehensive income (OCI) after IFRS implementation in the industrial sector of financial that is listed in the Indonesia Stock Exchange in 2012-2015. The sample in this research is 91 financial sector companies. The finance industry has 5 sub-sectors such as banking sub-sector, sub-sector financial institution sub sector, securities company sub sector, insurance sub sector and other sub sector. Analysis techniques in the study using cross tabulation analysis and the difference test was done by Cramer V test because of its nominal nature. Testing does not require the assumption of normality because it belongs to the nonparametric statistical group. The results of the hypothesis testing of the financial industry sector proved that the foreign exchange component, available for sale securities, hedge funds and associtions were found to be different, while the components of employee benefits and revaluation of assets were not found in the income statement and other comprehensive income.